2002
DOI: 10.1101/gad.222902
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative action of Tbx2 and Nkx2.5 inhibits ANF expression in the atrioventricular canal: implications for cardiac chamber formation

Abstract: During heart development, chamber myocardium forms locally from the embryonic myocardium of the tubular heart. The atrial natriuretic factor (ANF) gene is specifically expressed in this developing chamber myocardium and is one of the first hallmarks of chamber formation. We investigated the regulatory mechanism underlying this selective expression. Transgenic analysis shows that a small fragment of the ANF gene is responsible for the developmental pattern of endogenous ANF gene expression. Furthermore, this fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
353
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(376 citation statements)
references
References 60 publications
21
353
0
2
Order By: Relevance
“…Tbx2 forms a complex with Nkx2-5͞Csx on the site containing a T-box factor, located at position Ϫ250 bp, and an NK binding element, located at position Ϫ259 bp, within the ANF promoter and represses ANF promoter activity. In vivo inactivation of either site, such as AAGT of the NK binding element mutated to CCTC, eliminated the repression (50). These in vitro binding and in vivo functional studies indicate that the NK binding elements that are found in most of the known functional NK target sites are necessary either with or without cofactors.…”
Section: Discussionmentioning
confidence: 81%
“…Tbx2 forms a complex with Nkx2-5͞Csx on the site containing a T-box factor, located at position Ϫ250 bp, and an NK binding element, located at position Ϫ259 bp, within the ANF promoter and represses ANF promoter activity. In vivo inactivation of either site, such as AAGT of the NK binding element mutated to CCTC, eliminated the repression (50). These in vitro binding and in vivo functional studies indicate that the NK binding elements that are found in most of the known functional NK target sites are necessary either with or without cofactors.…”
Section: Discussionmentioning
confidence: 81%
“…For example, TBX1 haploinsufficiency causes DiGeorge syndrome and TBX5 haploinsufficiency results in HoltOram syndrome 9,10 . Targeted mutagenesis or knockdown of the genes encoding the T-box transcription factors demonstrates that Tbx1, Tbx2, Tbx3, Tbx5 (Tbx5a in zebrafish), Tbx18 and Tbx20 play essential roles during cardiac development in the mice or zebrafish [11][12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…How Irx4 promotes ventricular muscle gene expression is not yet known, nor do we understand how expression differences within subdomains of individual chambers are established. In addition, the interplay of the cardiac T-box transcription factors, Tbx2, -3, and -5, have been implicated in the regulation of the chamber-myocardium gene expression, although the precise mechanisms are still to be determined (Habets et al, 2002;Christoffels et al, 2004;Hoogaars et al, 2004). However, despite these advances, there remains much uncertainty surrounding the relationship between cardiac muscle formation and the generation of the distinct functions of the mature chambers of the vertebrate heart.…”
Section: Introductionmentioning
confidence: 99%